Dose‐escalation is needed for gross disease in high‐risk neuroblastoma. Issue 7 (22nd February 2018) - Casey, Dana L.; Kushner, Brian H.; Cheung, Nai‐Kong V.; Modak, Shakeel; LaQuaglia, Michael P.; Wolden, Suzanne L.
Abstract: Background: Locoregional failure is common after subtotal resection in high‐risk neuroblastoma. Although a dose of 21 Gy radiation therapy (RT) is standard for treatment of high‐risk neuroblastoma after gross total resection, the dose needed for local control of patients with gross residual disease at the time of RT is unknown. We sought to evaluate local control after 21–36 Gy RT in patients with high‐risk neuroblastoma undergoing subtotal resection. Methods: All patients with high‐risk neuroblastoma who received RT to their primary site from 2000 to 2016 were reviewed. Of the 331 patients who received consolidative RT to their primary site, 19 (5.7%) underwent subtotal resection and were included in our analysis. Local failure (LF) was correlated with biologic prognostic factors and dose of RT. Results: Median follow‐up among surviving patients was 6.0 years. Median RT dose was 25 Gy (range, 21 Gy–36 Gy). The 5‐year cumulative incidence of LF among all patients was 17.2%. LF at 5 years was 30% in those who received <30 Gy versus 0% in those who received 30–36 Gy ( P =  0.12). There was a trend towards improved local control in patients with tumor size ≤10 cm at diagnosis ( P =  0.12). The 5‐year event‐free and overall survival were 44.9% and 68.7%, respectively. Conclusion: After subtotal resection, patients who received less than 30 Gy had poor local control. Doses of 30–36 Gy are likely needed for optimal control of gross residual disease at the time of consolidative RT in high‐risk neuroblastoma.